Improvement of the storage and inventory management system for grocery stores to increase profits through the implementation of ABC classification and FIFO methodology - Cerquera Pérez, Luzmaría (2024)
In Peru, convenience stores or grocery stores, considered as micro and small businesses, play a significant role in the country's economy as they contribute substantially to the Gross Domestic Product (GDP). Moreover, they provide employment for a considerable number of people. In Lima, there are many stores without a digital system to manage their inventories, leading to inefficient organization. They rely on manual recording methods using notebooks, resulting in losses and high costs, negatively impacting their profits. This situation highlights a stagnation in the management of these small and medium-sized enterprises (SMEs) in this subsector due to declining profits, leading store owners to consider closing their businesses due to unprofitability. In response to this situation, a storage management model is needed to reduce losses in the stores. Therefore, the methodology proposed in this work is based on ABC classification, FIFO inventory policies, and product proximity, aiming to increase store profits by reducing losses and enhancing the overall shopping experience.